Attachment of Nucleosides and Other Linkers to Solid‐Phase Supports for Oligonucleotide Synthesis. Issue 1 (1st March 2013) - Guzaev, Andrei P.; Pon, Richard T.
Abstract: Specific step‐by‐step instructions for conversion of 5′‐ O ‐(4, 4′‐dimethoxytrityl)‐ and base‐protected nucleosides and other mono‐ O ‐(4, 4′‐dimethoxytrityl)‐protected diols to their hemisuccinate esters and their coupling to CPG (controlled‐pore glass) supports bearing aminopropyl or long chain aminoalkyl groups are presented. Additional guidelines are provided for selecting a coupling protocol and performing in‐process control. Curr. Protoc. Nucleic Acid Chem . 52:3.2.1‐3.2.23. © 2013 by John Wiley & Sons, Inc.